Self-medication in dentistry students at Paulista University, Goiânia – Goiás (Revista da Faculdade de Odontologia - UPF, 2012)
Introduction: Self-medication is a procedure fundamentally characterized by the sick person, or person responsible for his/her care, taking the initiative to obtain or produce and use a product they believe will bring benefits in the treatment of diseases or relief of symptoms. Dentists, together with doctors and veterinarians, comprise the professional classes that may and must prescribe medications for their patients. Therefore, it is believed that these individuals, as a result of their duties, are professionals that know, understand and make an ex-haustive study of medications. Objective and Methodology: Based on this, a research was conducted among the academic students of the dentistry course at Paulista University, Flamboyant campus – Goiânia, GO, Brazil, during which 209 questionnaires were applied among students from the 3rd to 8th periods. Results: The purpose of applying these questionnaires was to trace a profile with regard to the use of medications without medical prescription, and high incidence was found among academic students, both as regards the quantity of medications and variety of substances used. Conclusions: The result was an alert that irrespective of the individual’s knowledge, whether it involved a layperson or professional qualified for prescription, this habit repeated it. This is an alarming fact, because if the professional him/herself, who should educate patients and dissuade them from this practice, is a habitual user, it becomes more difficult to aspire to the future inhibition and reduction of this practice that is so harmful to health.